Molecular epidemiology of Echinococcus species in Pakistan - Khan, Aisha; Simsek, Sami; Ahmed, Haroon (Wolters Kluwer Medknow Publications, 2018)
[Abstract Not Available]
Keywords: Echinococcosis; Molecular; Genotyping; Pakistan